IPTEKS EVALUASI PEMBINAAN DAN PENGAWASAN PENYELENGGARAAN PEMERINTAHAN DAERAH PADA DINAS TENAGA KERJA DAN TRANSMIGRASI DAERAH PROVINSI SULAWESI UTARA - Mawuntu, Nikita Srisilia; Maradesa, Djeini (Universitas Sam Ratulangi, 2018)
Good governance is a requirement in every regional and central government. To ensure the good governance has proceeded well in the unity of government, then a regulation about guidance and supervision of the regional government is arranged which regulates all about the implementation of guidance and supervision in the regional government. The Official of Manpower and Transmigration of North Sulawesi Province is one of the official agencies that has a large workload and has implemented the internal guidance and supervision in accordance with applicable regulations. This was assessed based on the Regulation of Republic of Indonesia’s Government No. 12 of 2017 concerning the Guidance and Supervision of the Implementation of Regional Government. And in order to support the realization of a good government system in the North Sulawesi Province, the Department of Manpower and Transmigration continues to strive to maintain the process that has been carried out.Keywords: good governance, guidance, supervision, regional government